Course of Magnetic Resonance Imaging–Detected Inflammation and Structural Lesions in the Sacroiliac Joints of Patients in the Randomized, Double‐Blind, Placebo‐Controlled Danish Multicenter Study of Adalimumab in Spondyloarthritis, as Assessed by the Berlin and Spondyloarthritis Research Consortium of Canada Methods. Issue 2 (February 2016) - Pedersen, Susanne J.; Poddubnyy, Denis; Sørensen, Inge J.; Loft, Anne‐Gitte; Hindrup, Jens S.; Thamsborg, Gorm; Asmussen, Karsten; Hendricks, Oliver; Nørregaard, Jesper; Piil, Anne‐Dorthe; Møller, Jakob M.; Jurik, Anne‐Grethe; et al.
Abstract : Objective: To investigate changes in magnetic resonance imaging (MRI)–assessed inflammation and structural lesions in the sacroiliac (SI) joints during treatment with adalimumab versus placebo. Methods: In a 48‐week double‐blind, placebo‐controlled trial, 52 patients with spondyloarthritis were randomized to receive subcutaneous injections of either adalimumab 40 mg (n = 25) or placebo (n = 27) every other week for 12 weeks. Patients in the adalimumab group continued to receive and patients in the placebo group were switched to adalimumab 40 mg every other week for an additional 12 weeks. MRI of the SI joints was performed at weeks 0, 12, 24, and 48, and the images were assessed independently in a blinded manner using the modified Berlin and the Spondyloarthritis Research Consortium of Canada (SPARCC) MRI scores for inflammation and structural lesions of the SI joints. Results: At baseline, 56% of the adalimumab group and ∼72% of the placebo group had an MRI‐assessed inflammation score of ≥1. Among the patients with inflammation at baseline, the mean percent reductions in MRI scores for inflammation from week 0 to 12 were greater in the adalimumab group compared with the placebo group (Berlin method, −62% versus −5%; SPARCC method, −58% versus −12% [both P < 0.04]). Furthermore, the mean SPARCC erosion score decreased (−0.6) and the SPARCC backfill score increased (+0.8) in the adalimumab group from week 0 to week 12. From week 12 to week 24, larger absolute reductions in the Berlin/SPARCC inflammation scores and the SPARCC erosion score and larger increases in the Berlin/SPARCC fatty lesion scores were seen in the placebo group compared with the adalimumab group. In univariate regression analyses (analysis of covariance) and multivariate stepwise regression analyses, treatment with adalimumab was independently associated with regression of the SPARCC erosion score from week 0 to 12 but not with changes in the other types of MRI lesions. Conclusion: Significant changes in the Berlin and SPARCC MRI‐assessed inflammation scores and in the SPARCC MRI‐assessed erosion scores occurred within 12 weeks after initiation of adalimumab. Tumor necrosis factor inhibitor treatment was associated with resolution of erosions and the development of backfill.